IS BMI REALLY SUITABLE FOR CHARACTERIZATION OF PHYSIQUE (NOURISHED STATE, STATURE) AND OPTIMUM BODYWEIGHT OF ATHLETES? - Andras S. Szabo; Pal Tolnay (Sport Scientific And Practical Aspects, 2025)
Body Mass Index (BMI) is not perfectly (sometimes absolutely not) suitable for determination of the nourished state (physique) and optimum body-weight for athletes because of 3 reasons. 2 reasons are general and the third one is of specific character. The first one is, that the human bodymass is proportional to the third extent and not to the second one of the linear measurement (here height), that is proportional to the volume (and not the surface!) of the body. So instead of BMI the Rohrer-index is proposed to use. The second, still general reason, that only height and body-mass are not enough for appropriate characterization and estimation of the physique, figure and ideal bodymass, because as a function of body structure (e.g. parameters of width) the optimum bodymass can even show 20-25 kg difference among individuals having the same height. The third specific reason is that the athletes can have in general much higher muscle-ratio (instead of 43 % for average adult men even over 60 %) than normal human beings, non sportsmen, so BMI even more than 30 should be eventually evaluated as a normalweight, and not overweight or obesity.